2015
DOI: 10.1080/00222895.2014.931273
|View full text |Cite
|
Sign up to set email alerts
|

Science-Based Neurorehabilitation: Recommendations for Neurorehabilitation From Basic Science

Abstract: Neuroscience has fundamentally changed the understanding of learning and memory within recent years. Here, the authors discuss a number of specific areas where they believe new understanding of the CNS from basic science is having a fundamental impact on neurorehabilitation and is leading to new therapeutic approaches. These areas have constituted a basis for development of some basic principles for neurorehabilitation: Optimal rehabilitation should involve (a) active (patient) participation in the training, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(66 citation statements)
references
References 97 publications
2
62
0
Order By: Relevance
“…This is a very important point to consider in designing an exercise clinical trial for persons with dementia as well as in generalizing and applying the results in routine practice settings. Optimal rehabilitation training should involve the active participation of the patient as opposed to passive manipulation (Katalinic, Harvey, & Herbert, 2011; Nielsen, Willersley-Olsen, Christiansen, Lundbye-Jensen, & Lorentzen, 2015). The other key components of an optimal rehabilitation program include challenging the skill of the person training, motivating and rewarding, intensive training for as long a period of time that is feasible, and carefully organizing the training in the setting of other activities (Nielsen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a very important point to consider in designing an exercise clinical trial for persons with dementia as well as in generalizing and applying the results in routine practice settings. Optimal rehabilitation training should involve the active participation of the patient as opposed to passive manipulation (Katalinic, Harvey, & Herbert, 2011; Nielsen, Willersley-Olsen, Christiansen, Lundbye-Jensen, & Lorentzen, 2015). The other key components of an optimal rehabilitation program include challenging the skill of the person training, motivating and rewarding, intensive training for as long a period of time that is feasible, and carefully organizing the training in the setting of other activities (Nielsen et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Optimal rehabilitation training should involve the active participation of the patient as opposed to passive manipulation (Katalinic, Harvey, & Herbert, 2011; Nielsen, Willersley-Olsen, Christiansen, Lundbye-Jensen, & Lorentzen, 2015). The other key components of an optimal rehabilitation program include challenging the skill of the person training, motivating and rewarding, intensive training for as long a period of time that is feasible, and carefully organizing the training in the setting of other activities (Nielsen et al, 2015). Importantly, the patients and caregivers need to understand that consistent training several times a week will be part of the rest of their lives if they want to maintain any potential benefits.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with many studies on skill acquisition from a wide range of disciplines, we found that gradually increasing the difficulty of a task is beneficial for acquiring a motor skill. Choosing an adequate initial task complexity and increasing the complexity in relation to the improvement during learning, is seen as important prerequisite for efficient motor learning and is, thus, commonly used as training principle in sports as well as in rehabilitation 16,45 . The theoretical relationship between task difficulty, skill level and learning was systematically described in the "challenge point" framework 46 .…”
Section: Gradual Task-difficulty Facilitates Skill Acquisition By Meamentioning
confidence: 99%
“…In the motor learning theory, this is essential to promote control of postural mechanisms involved in the yoga postures and movements. 13 The occupational therapist provided sensory cues and props that matched the yoga video in order to increase student engagement. The speech therapist promoted interaction among the students in the class by increasing awareness and turn taking as appropriate.…”
Section: Participantsmentioning
confidence: 99%